THE DEVELOPMENT OF ENGLISH LEARNING MODEL BASED ON CONTEXTUAL TEACHING AND LEARNING (CTL) IN JUNIOR HIGH SCHOOLS - Munir, Munir; Nur, Riola Haya (Universitas Negeri Makassar, 2018)
Specific targets of this research are: (1) Lesson Plan (RPP) for junior high school students, (2) Student Worksheet; and CTL-based student books. The long-term goal to be achieved is the occurrence of a CTL-based English language learning process that can improve the English language skills of junior high school students in South Sulawesi. The method used to achieve the purpose of this research is Research and Development (R & D) by studying a number of models of learning device development, to further select and apply the device development model by the characteristics of subjects and background of psychology development of junior high school students. Repeated trials of instructional devices were conducted to obtain the best prototype learning tools that meet the needs of junior high school students in South Sulawesi. The results of data analysis show that (1) one way to improve students' communication skill and their critical thinking ability is by developing learning tools based on CTL English; (2) the factors that affect the inability to communicate in English is not the occurrence of English learning process that provides opportunities for students to use English maximal in the classroom. This is in contrast to the learning process undertaken with CTL-based learning where students have the opportunity to speak and think critically to discuss the real problems faced in front of their classmates to maintain the results of the projects they report. In addition, with the learning tools based on CTL, it was also found that the ability to interact in English students with classmates as well as to teachers also seemed to increase.